2013
DOI: 10.1007/s12272-013-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

A new phenanthrene derivative and two diarylheptanoids from the roots of Brassica rapa ssp. campestris inhibit the growth of cancer cell lines and LDL-oxidation

Abstract: Brassica rapa ssp. campestris (Brassicaceae) is a conical, deep purple, edible root vegetable commonly known as a turnip. We initiated phytochemical and pharmacological studies to search for biological active compounds from the roots of B. rapa ssp. campestris. We isolated a novel phenanthrene derivative, 6-methoxy-1-[10-methoxy-7-(3-methylbut-2-enyl)phenanthren-3-yl]undecane-2,4-dione, named brassicaphenanthrene A (3) along with two known diarylheptanoid compounds, 6-paradol (1) and trans-6-shogaol (2), throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Materials. BrPa was isolated from B. rapa by a previously described method (15). all cell culture reagents were purchased from Gibco; Thermo Fisher Scientific, inc.. all inhibitors were purchased from calbiochem.…”
Section: Brassicaphenanthrene a From Brassica Rapa Protects Ht22 Neuronal Cells Through The Regulation Of Nrf2-mediated Heme Oxygenase-1 mentioning
confidence: 99%
“…Materials. BrPa was isolated from B. rapa by a previously described method (15). all cell culture reagents were purchased from Gibco; Thermo Fisher Scientific, inc.. all inhibitors were purchased from calbiochem.…”
Section: Brassicaphenanthrene a From Brassica Rapa Protects Ht22 Neuronal Cells Through The Regulation Of Nrf2-mediated Heme Oxygenase-1 mentioning
confidence: 99%
“…The results showed that BRARBP extract and identified compounds were not cytotoxic and are in agreement with the previously reported studies of Wu et al (2013) on Brassica rapa spp. Campestris (Wu et al, 2013).…”
Section: Effect Of Brarp Extract On C Elegans Gut Model Against Ementioning
confidence: 99%
“…Another investigation showed that 2‐phenylethyl isothiocyanate ( 21 ) and benzyl isothiocyanate ( 36 ) could reduce benzo( a ) pyrene‐induced lung tumorigenesis by the activation of MAP kinases, AP‐1 transcription factors and p53 phosphorylation when conjugated with N ‐acetylcysteine (Lopez‐herrera et al., ). Similar to isothiocyanates, brassicaphenanthrene A ( 110 ), a novel phenanthrene derivative, and two known diarylheptanoids, 6‐paradol ( 108 ) and trans ‐6‐shogaol ( 109 ) showed high inhibition against the growth of human cancer lines (HCT‐116, MCF‐7, and HeLa, IC 50 values ranging from 15.0 to 35.0 μM) and against LDL‐oxidation (IC 50 values ranging from 2.9 to 7.1 μM) (Wu et al., ). A further study on three cancer cell lines (Hep‐2, AMN‐3 and Hela) in vitro revealed that the aqueous extract of turnip showed high inhibition against ANM‐3 (63%) and Hep‐2 (42%) cells at a concentration of 1250 μg/mL, and against Hela cells (64%) at a concentration of 10 mg/mL (Barakat, Obaid, Ali, Hassan, & Abaas, ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%